Piecewise-linear companding transform for peak-to-average power ratio reduction of OFDM signals - YANG Pin-lu; HU Ai-qun (Tongxin xuebao)
In order to reduce the peak-to-average power ratio（PAPR） of orthogonal frequency division multiplexing（OFDM） signals,a piecewise-linear companding transform was proposed.Small amplitudes were multiplied by a scale factor,while large ones were not only multiplied by a scale factor but also added by a shift.The resulting companding transform was piecewise-linear and continuous.It can provide significant PAPR reduction performance with low compu-tational complexity,and has low influence on system performances through piecewise transform.It is shown by theoreti-cal analysis and simulation that,a good trade-off between PAPR reduction and bit-error-rate performances can be achieved by carefully choosing the two scales and the shift.Furthermore,compared with existing linear and nonlinear companding transforms,a better power spectral density performance can be achieved.